A 2-Stage Reconstruction of the Jaw Using Vascularized Bone and Secondary Alveolar Ridge Augmentation With Particulate Cancellous Bone and Marrow. Issue 2 (April 2016) - Saijo, Hideto; Sugiyama, Madoka; Kanno, Yuki; Ohkubo, Kazumi; Hoshi, Kazuto; Takato, Tsuyoshi
Abstract : Purpose: To present the novel technique for reconstruction of the jaw, that facilitates occlusal restoration using dental implants, in cases with wide bony defects from tumor resection. Materials and Methods: After alveolar ridge is augmented using titanium mesh tray and particulate cancellous bone and marrow (PCBM) from iliac bone on reconstructed bone, by way of improvement of maxillomandibular relationship for dental implants. Results: This 2-stage surgery underwent successfully in 3 cases. After 2-stage surgery and occlusal reconstruction using dental implant, the patients experienced no complications, and received satisfaction with results functionally and aesthetically. Conclusions: Our results suggest that, in cases where bone defect is over a wide area, in addition to vascularized bone grafts, secondary alveolar ridge augmentation using a titanium mesh tray and PCBM on grafted bone can provide satisfactory occlusion further to improvement of facial form.